Habib Jafar's Role in Prophetic Communication on the “6 Religious Leaders Unite” Podcast - Fariza, Muhammad Rio; Sofyan, Khoridho Abdillah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This study examines the articulation of prophetic communication values in interfaith dialogue as performed by Habib Jafar in the podcast Login, Season 2, Episode 6, titled “Pemuka Agama Jadi Satu di Lebaran” (“Religious Leaders Unite During Eid”). Employing qualitative content analysis, this research analyzes podcast transcripts alongside visual and non-verbal communication elements. The findings reveal that Habib Jafar operationalizes three core dimensions of prophetic communication, namely humanization, liberation, and transcendence. Humanization is enacted through empathetic engagement and contextual understanding of others’ lived experiences, while liberation is expressed by encouraging critical and independent thinking. Transcendence emerges through invitations to spiritual reflection and the cultivation of a deeper relationship with God. Through these communicative strategies, Habib Jafar conveys inclusive da‘wah messages that facilitate interfaith dialogue and foster mutual understanding across religious communities. This study contributes to communication and religious studies by demonstrating how prophetic communication can be strategically embedded in digital media to bridge interreligious divides and promote universal ethical values in a rapidly evolving information environment.